1. AT HOME AND IN THE WORKPLACE: A HISTORICAL INTRODUCTION TO THE "SPATIAL TURN". Issue 3 (9th October 2013) - KÜMIN, BEAT; USBORNE, CORNELIE
ABSTRACT This introduction places the forum contributions in the wider context of the "spatial turn" within the humanities and social sciences. Following a survey of the historical trajectories of the field, a review of impulses from different disciplines, and a sketch of general developments over the last few decades, the editors exemplify key approaches, methods, and conceptual advances with reference to gender studies. The focus then turns to the structure, main themes, and specific contents of this collection, which features both case studies and theoretical reflections. In conclusion, the essay underlines the significance and further potential of the "spatial turn."